Goat milk and caddies – A Muslim community in Cha Am, Thailand - Marja-Leena Heikkilä-Horn (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
This paper looks at the history of a Muslim village and its interaction with the surrounding establishments.The Muslim village Baan Yai is located just adjacent to one of the huge golf courses of Hua Hin, an upscale, traditional beach resort accommodating the Summer Palace of the King Rama IX and offering world-class golf courses. Even though the village is close to one of the three university campuses and a golf course, the latter are unaware of its existence. The paper also raises the question of the role of this community in the wider ummah both in Thailand and overseas while presenting a brief discussion of relevant aspects of the history of Thai Muslims. The paper concludes that while the villagers might be reasonably knowledgeable about basic Islamic teachings and practices, they appear to be detached from the Islamic origins and history of the community. This relative historical discontinuity is only matched by deliberate spatial fragmentation caused by the administrative structure of the village